Performing Arts Management in Inclusive Early Chidlhood Education KB-TK Talenta Semarang - Rahmawati, Ati; Adiarti, Wulan (BELIA: Early Childhood Education Papers, 2018)
KB-TK Talenta Semarang is inclusive schools that has an annual program performing arts and graduatation of group B kindegarten students who receive graduation state. Performing arts is an appreciation activity to develop children’s competence. In inclusive schools, performing arts purpose to stimulate sympathy and tolerance among reguler students and inclusive students. Guidance and direction from the teacher required students to follow the preparation process until the performance. The purpose of this study was to describe performing arts management including planning, organizing, actuating and controlling  in early childhood education of KB-TK Talenta Semarang. This research used qualitative approach, and the data collection techniques used the observation methode, documentation and interviews. The subjects of this research were the responsible of activity, the activity coordinator, the responsible of event, the vocal choach, and  the dance coach. The data resource obtained were from the subjects, literature review, and document. The data analysis tecniques was done using interactive models by miles and huberman. Based on the results of data analysis, the performing arts management in Inclusive early childhood of KB-TK Talenta Semarang included: Planning began with the determination of theme and the process of cultivation that requires classroom teacher’s room in assisting disability students, during practice, rehearsal and performance. Organizing was a work system that was applied, based on the structure of the committee that was formed. The types of performances offered were vocals, dance and opera. There was a responsible for directing disability students while on stage. Controlling was carried out by the responsible of activity, either through observation or accountability report. The sequence of this process goes flexibly and adjusts the ability of commitee, appearance needs and real conditions in location.   Keywords: Performing arts management, invlusive early childhood education